Comparison of Clinician Judgments and Measurements of Swallow Response Time: A Preliminary Report. - Karnell, Michael P.; Rogus, Nicole M. (Journal of Speech, Language & Hearing Research, 2005)
Practicing clinicians frequently offer judgments about aspects of swallowing physiology rather than performing actual measurements. Little is known about the accuracy of those judgments. The purpose of this preliminary study was to explore agreement of clinicians' judgments of pharyngeal swallow response time (PSRT) with temporal measurements of PSRT. In preparation for a larger study, PSRT was measured from the first 3 ml liquid bolus swallow that appeared in each of 20 videofluorographic swallowing evaluations. The same 20 swallows were then shown to 3 clinicians who were instructed to subjectively rate PSRT. The reliability of the PSRT measurements was strong (r>.95). Intrajudge and interjudge agreement was better than chance in all but 1 interjudge comparison. Percentage agreement between clinicians' judgments and the measurements, when the measurements were categorized as either not delayed or delayed, ranged from 60% to 95%. Chi-square and Phi statistics comparing the outcomes of clinicians' ratings with the measurement outcomes were significant, supporting the agreement of the judgments with the measurements. Although the results of tests of agreement were found to be acceptable, clinician experience and training remain important issues whenever clinical judgments are involved. Larger studies are needed to establish the accuracy and importance of clinicians' judgments of PSRT and observations of swallowing physiology. Reprinted by permission of the publisher.